Kebijakan Penanggulangan Kemiskinan Desa Melalui Program Kanggo Riko di Kabupaten Banyuwangi - Auliya Gaffar Rahman (Biram Samtani Sains, 2026)
This article examines Banyuwangi Regency’s Kanggo Riko as a village-centered anti-poverty policy that couples productive asset support for poor households with local governance mechanisms and digital monitoring. Using a qualitative–descriptive design with Creswell’s data analysis steps (data organization, coding, theme development, interpretation), we synthesize official regulations, government releases, and village decrees. The program, enacted by Regent Regulation No. 31/2018, provides in-kind business tools worth IDR 2.5 million for registered poor households—prioritizing female-headed households—selected through DTKS and village verification. In 2024, the package added six-month BPJS Ketenagakerjaan coverage; the annual target was 1,890 recipients. Village-level SKs show on-the-ground determination of beneficiaries, while the SPBE architecture lists a dedicated Kanggo Riko application for by-name, by-address monitoring. Contextualized by BPS data showing poverty fell from 7.34% (March 2023) to 6.54% (March 2024), findings indicate a coherent policy bundle linking household livelihood support, local institutionalization, and information systems to reinforce poverty reduction.